Molecular systematics of the freshwater stingrays (Myliobatiformes: potamotrygonidae) of the Amazon, Orinoco, Magdalena, Esequibo, Caribe and Maracaibo basins (Colombia-Venezuela): Evidence from mitochondrial genes (2012)
Freshwater stingrays from the family Potamotrygonidae have a restricted distribution to the freshwater systems of South America. Lack of adequate information about the taxonomic and evolutionary relationships, ecology, biology and distribution of several species belonging to this family makes them vulnerable to anthropic activities, including commercial exploitation for the ornamental fish market. Samples were collected from the main river basins in Colombia and Venezuela (Amazon, Orinoco, Magdalena, Esequibo, Caribe and Maracaibo) for four genera and seven species of the family (Heliotrygon gomesi, Paratrygon aiereba, Plesiotrygon iwamae, Potamotrygon motoro, Potamotrygon yepezi, Potamotrygon schroederi, Potamotrygon magdalenae), and some unidentified species. Molecular markers Cytochrome Oxidase subunit I, Cytochrome b and ATPase subunit 6 were amplified and sequenced. Maximum likelihood and Bayesian Inference analysis were performed to obtain topologies for each marker and for a concatenated dataset including the three genes. Small dataset may compromise some methods estimations of sequence divergence in the ATP6 marker. Monophyly of the four genera in the Potamotrygonidae family was confirmed and phylogenetic relations among member of the Potamotrygon genus were not clearly resolved. However, results obtained with the molecular marker Cytb appear to offer a good starting point to differentiate among genera and species as a tool that could be used for fast molecular identification (Barcode). The application of this gene as a barcode could provide a useful tool than can be applied for Management and regulation of extraction practices for these genera. Sequencing of complete mitochondrial genomes would be the next step for testing evolutionary hypothesis among these genera. Population studies should be undertaken for Potamotrygon magdalenae, Paratrygon aiereba and Potamotrygon motoro to establish possible population differentiation among basins, information that is key for delineating conservation and management plans for these species.